El impacto de las políticas de apoyo post- adopción en la seguridad jurídica de las familias adoptivas. - Pupiales Cañamar, María Belén (2024)
Post-adoption support policies in Ecuador are essential to guarantee the legal security and well-being of adoptive families. Research shows that well-structured support significantly improves the legal and social stability of these families, facilitating the adaptation of adopted children and strengthening family cohesion. The study used a qualitative methodology to explore the experiences of families and professionals involved, combined with a documentary analysis of current policies and their evolution over time. Theoretical methods such as analytical-synthetic were used to evaluate policies, inductive-deductive to examine specific cases and draw general conclusions, and historical-logical to trace the evolution of these policies. Data collection was conducted through unstructured interviews with legal professionals specializing in adoptions in the city of Ibarra, using a flexible guide to address relevant topics in depth. The results indicate that effective support policies not only improve legal stability, but also facilitate the child's adaptation and strengthen family ties. Recommendations include the implementation and continuous improvement of post-adoption support programs, ongoing training of the professionals involved, and the creation of feedback mechanisms to adjust policies based on the experiences of families. This will allow for a more harmonious and secure integration within the legal framework, promoting a successful and lasting transition for adoptive families and the children they foster.